PERAN PETUGAS REKAM MEDIS DALAM PELAKSANAAN VAKSINASI COVID-19 DI PUSKESMAS X KAB. BANDUNG BARAT: - - Novi Nurjayanti; Yovita Tri Katarina - (Jurnal Kesehatan, 2022)
The implementation of the Covid-19 vaccination is one of the national programs that must also be carried out in all health services involving all health workers, including medical record officers. The role of the Medical Record Officer in the implementation of the Covid-19 vaccination is one that supports the achievement of the target for the implementation of the Covid-19 vaccination in health services. This study aims to determine the role of medical record officers in the implementation of Covid-19 vaccination at Community Health Center (Puskesmas) X West Bandung Regency. The type of research used is descriptive qualitative with data collection techniques using interviews and direct observation. The data analysis technique uses Miles and Huberman with the data validity technique using an extension of participation. The subjects of this study were 3 medical record personnel who were involved in the implementation of the covid-19 vaccination at Community Health Center (Puskesmas) X West Bandung Regency based on the snowball technique. The results showed that the role of the medical record officer at the time of the covid-19 vaccination was as an interviewer, in charge of p-care access and data input, password holder, observer and reporting officer.